2021
DOI: 10.1111/trf.16690
|View full text |Cite
|
Sign up to set email alerts
|

Hemolytic anemia blunts the cytokine response to transfusion of older red blood cells in mice and dogs

Abstract: Background: Transfusion of red blood cells (RBCs) stored for longer durations induces hemolysis and inflammatory cytokine production in murine and canine models. Despite immune system activation by stored RBCs, human randomized trials suggest that fresher RBC transfusions do not improve clinical outcomes. We hypothesized that underlying recipient hemolysis may affect cytokine responses to older RBC transfusions. Study design and methods: C57BL/6 mouse cohorts were infused with anti-TER119 antibody to induce he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…2 Because standard RBC units contain ˜200-250 mg of haemoglobin iron, rapid post-transfusion clearance of significant numbers of storage-damaged RBCs overwhelms the monocyte/macrophage system, 3 thereby releasing significant amounts of haemoglobin iron into the circulation in both animal models and humans. [4][5][6][7] The rate of iron release can be sufficient to saturate transferrin, the physiologic iron transporter in the circulation, thereby producing non-transferrin-bound iron (NTBI). 7 NTBI promotes proliferation and virulence of specific siderophilic bacterial species; thus, hepcidin-mediated elimination of NTBI may be an important mechanism of host defence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Because standard RBC units contain ˜200-250 mg of haemoglobin iron, rapid post-transfusion clearance of significant numbers of storage-damaged RBCs overwhelms the monocyte/macrophage system, 3 thereby releasing significant amounts of haemoglobin iron into the circulation in both animal models and humans. [4][5][6][7] The rate of iron release can be sufficient to saturate transferrin, the physiologic iron transporter in the circulation, thereby producing non-transferrin-bound iron (NTBI). 7 NTBI promotes proliferation and virulence of specific siderophilic bacterial species; thus, hepcidin-mediated elimination of NTBI may be an important mechanism of host defence.…”
Section: Introductionmentioning
confidence: 99%
“…the ‘RBC storage lesion’), thus impairing their transfusion quality and circulatory lifespan post‐transfusion 2 . Because standard RBC units contain ˜200–250 mg of haemoglobin iron, rapid post‐transfusion clearance of significant numbers of storage‐damaged RBCs overwhelms the monocyte/macrophage system, 3 thereby releasing significant amounts of haemoglobin iron into the circulation in both animal models and humans 4–7 . The rate of iron release can be sufficient to saturate transferrin, the physiologic iron transporter in the circulation, thereby producing non‐transferrin‐bound iron (NTBI) 7 .…”
Section: Introductionmentioning
confidence: 99%
“…However, the study by Muenster et al exposed erythrocyte concentrates to oxygen or nitric oxide prior to transfusion [21]. (C) In 13 out of the 36 included studies, a total of 440 dogs were included, with only three studies describing a repeated use of the same animals [14,[42][43][44][45][46][47][48][49][50][51][52][53]. Study populations showed similar ranges compared to the other two species, with studies using six to 76 dogs per study [14,[42][43][44][45][46][47][48][49][50][51][52][53].…”
Section: Basic Study Characteristicsmentioning
confidence: 99%
“…(C) In 13 out of the 36 included studies, a total of 440 dogs were included, with only three studies describing a repeated use of the same animals [14,[42][43][44][45][46][47][48][49][50][51][52][53]. Study populations showed similar ranges compared to the other two species, with studies using six to 76 dogs per study [14,[42][43][44][45][46][47][48][49][50][51][52][53]. In three out of 13 publications, male and female dogs were included in the same study [42,50,53].…”
Section: Basic Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation